Echa "Idź i patrz" Elema Klimowa w dwóch polskich filmach antywojennych – "Mieście 44" Jana Komasy oraz "Wołyniu" Wojciecha Smarzowskiego - Andrzej Szpulak (Images)
The subject of interest in this text are the relations between the famous Elem Klimow’s Come and See and two Polish movies made in the second decade of the 21st century – Jan Komasa’s Warsaw 44 and Wojciech Smarzowski’s Wołyń. These relations are considered at the genetic level, the level of historical references, the genological level and the plane of audiovisual material created in films. The analysis leads to the conclusion that genological issues play the most important role in building these relationships, among them the shape of the main character’s figure.The text can be treated as a contribution to reflection on the genre distinctiveness of the anti-war film.